Iran's Influence : a Religious-Political State and Society in its Region. - Rostami-Povey, Elaheh (Zed Books Ltd., 2010)
There is a saying in Arabic: me and my brother against my cousin, and me and my cousin against the outsider. Iran's Influence is the first comprehensive analysis of the role that Iran plays in Middle Eastern and global politics. Expert Iranian author Elaheh Rostami-Povey provides a fascinating introduction to one of the Middle East's most controversial and misunderstood countries. Based on several years of original research carried out both in Iran and across the region, this insightful guide presents essential new ideas to help the reader understand the Middle East.